Diagnostic accuracy of glabellar tap sign for Parkinson's disease - Nuuttila Simo; Eklund Mikael; Joutsa Juho; Jaakkola Elina; Mäkinen Elina; Honkanen Emma A; Lindholm Kari; Noponen Tommi; Ihalainen Toni; Murtomäki Kirsi; Nojonen Tanja; Levo Reeta; et al. (SPRINGER WIEN, 2022)
Glabellar tap or reflex (GR) is an old bedside clinical test used in the diagnostics of Parkinson's disease (PD), but its diagnostic value is unclear. This study examines the diagnostic validity and reliability of GR in PD in relation to brain dopaminergic activity. GR was performed on 161 patients with PD, 47 patients with essential tremor (ET) and 40 healthy controls immediately prior to dopamine transporter (DAT) [123I]FP-CIT SPECT scanning. The binding ratios were investigated with consideration of the GR result (normal/abnormal). In addition, the consistency of the GR was investigated with 89 patients after a mean follow-up of 2.2 years. PD and ET patients had higher GR scores than healthy controls (p < 0.001), but there was no difference in GR between PD and ET patients (p = 0.09). There were no differences in the ratio of abnormal to normal GRs between the PD and ET groups (73% vs. 64% abnormal, respectively, p = 0.13) or in DAT binding between PD patients with abnormal and normal GRs (p > 0.36). Over follow-up, the GR changed from abnormal to normal in 20% of PD patients despite the presence of clinically typical disease. The sensitivity and specificity of GR for differentiating PD from ET were 78.3% and 36.2%, respectively. Although GR has been used by clinicians in the diagnostics of PD, it does not separate PD from ET. It also shows considerable inconsistency over time, and abnormal GR has no relationship with dopamine loss. Its usefulness should be tested for other clinical diagnostic purposes.